HUBUNGAN LAMA STUDI DENGAN NILAI UJIAN KOMPREHENSIF MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA IAIN BUKITTINGGI - Medika, Gema Hista; Tomi, Zebbil Billian (Sainstek : Jurnal Sains dan Teknologi, 2020)
This study aimed to see the correlation between length of study and comprehensive test scores. This correlational study employed a quantitative approach. The population was 43 graduates of Class XI of Mathematics Education Study Program IAIN Bukittinggi in 2019. The data in this study were length of study and comprehensive test scores. The data were analyzed using the Spearman's Test because the data were not normally distributed with a significant ? = 5%. The results showed that there was no significant correlation between length of study and comprehensive test scores with the very low category and a negative direction (sig 0.467> 0.05). Correlation value of -0.114 indicated a very low relationship with a negative direction.